Management Strategies for Aggressive Cushing's Syndrome: From Macroadenomas to Ectopics - Carlotta Pozza (Journal of Oncology, 2012)
Cushing’s syndrome (CS) is a rare but severe clinical condition represented by an excessive endogenous cortisol secretion and hence excess circulating free cortisol, characterized by loss of the normal feedback regulation and circadian rhythm of the hypothalamic-pituitary axis due to inappropriate secretion of ACTH from a pituitary tumor (Cushing’s disease, CD) or an ectopic source (ectopic ACTH secretion, EAS). The remaining causes (20%) are ACTH independent. As soon as the diagnosis is established, the therapeutic goal is the removal of the tumor. Whenever surgery is not curative, management of patients with CS requires a major effort to control hypercortisolemia and associated symptoms. A multidisciplinary approach that includes endocrinologists, neurosurgeons, oncologists, and radiotherapists should be adopted. This paper will focus on traditional and novel medical therapy for aggressive ACTH-dependent CS. Several drugs are able to reduce cortisol levels. Their mechanism of action involves blocking adrenal steroidogenesis (ketoconazole, metyrapone, aminoglutethimide, mitotane, etomidate) or inhibiting the peripheral action of cortisol through blocking its receptors (mifepristone “RU-486”). Other drugs include centrally acting agents (dopamine agonists, somatostatin receptor agonists, retinoic acid, peroxisome proliferator-activated receptor γ “PPAR-γ” ligands) and novel chemotherapeutic agents (temozolomide and tyrosine kinase inhibitors) which have a significant activity against aggressive pituitary or ectopic tumors.